A Monte Carlo study of the spectra from inhomogeneous accretion flow. (August 2017) - Yu, Xiao-Di; Li, Ya-Ping; Xie, Fu-Guo; Ma, Ren-Yi
Abstract: A model of an inhomogeneous accretion flow, in which cold clumps are surrounded by hot gas or corona, has been proposed to explain the spectral features of black hole X-ray binaries. In this work, we try to find possible observational features in the continuum that can indicate the existence of clumps. The spectra of an inhomogeneous accretion flow are calculated via the Monte Carlo method. Since the corresponding accretion flow is unsteady and complex, the accretion flow is described by a set of free parameters, the ranges of which can include the real cases. The influences of the parameters are investigated. It is found that the thermal component of the spectra deviates from multi-color black body spectra in the middle power-law part. On one hand, a warp appears due to the gaps between the clumps and the outer cold disk, and on the other hand, the slope of the line connecting the thermal peaks deviates from 4/3. The warp feature, as well as the correlation between the thermal peak at higher frequency and the spectral index, possibly indicate the existence of clumps, and are worthy of further investigation with more self-consistent models.